Agroecology: A Fertile Field for Human Computation - Hanappe, Peter; Dunlop, Rob; Maes, Annemie; Steels, Luc; Duval, Nicolas (Human Computation, 2016)
Agroecology -- the science of sustainable agriculture -- offers a new and positive perspective for the creation of sustainable food systems. We argue that, from the outset, it is important to involve citizens in this development to create the necessary, bottom-up support for change in agriculture and to re-establish the ties between food production and consumption. Human Computation and Citizen Science offer opportunities to include citizens in the planning, monitoring and evaluation of agro-ecosystems. In the P2P Food Lab project, we also seek new ways to engage them more creatively by setting up a shared online/offline platform in which they can learn, practice, innovate, and share observations on agroecological techniques. This paper gives a description and the underlying motivations of our ongoing work.